2017
DOI: 10.1186/s12879-017-2868-9
|View full text |Cite
|
Sign up to set email alerts
|

A clinical tool to predict Plasmodium vivax recurrence in Malaysia

Abstract: BackgroundRecurrence rates of Plasmodium vivax infections differ across various geographic regions. Interestingly, South-East Asia and the Asia-Pacific region are documented to exhibit the most frequent recurrence incidences. Identifying patients at a higher risk for recurrences gives valuable information in strengthening the efforts to control P. vivax infections. The aim of the study was to develop a tool to identify P. vivax- infected patients that are at a higher risk of recurrence in Malaysia.MethodsPatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In 2010, of the 5819 reported cases, approximately 60% were due to P. vivax [3]. Moreover, the potential for reactivation of dormant hypnozoites creates a number of difficulties for the elimination of malaria in the country [73]. The dramatic reduction of P. vivax observed in the present study also follows a steady increase in notification rate of P. malariae/P.…”
Section: Discussionsupporting
confidence: 57%
“…In 2010, of the 5819 reported cases, approximately 60% were due to P. vivax [3]. Moreover, the potential for reactivation of dormant hypnozoites creates a number of difficulties for the elimination of malaria in the country [73]. The dramatic reduction of P. vivax observed in the present study also follows a steady increase in notification rate of P. malariae/P.…”
Section: Discussionsupporting
confidence: 57%
“…The efficacy of antimalarials are reported to reduce malaria infection with a parasite reduction ratio of approximately 10,000 per erythrocytic cycle for artemisinin, and lower in quinolines 23 , demonstrating the effect of higher initial parasite level and longer clearance time. In addition, a higher parasite count has shown to contribute to a higher risk of recurrence 22 , supporting the risks of complications associated with a higher initial parasite level. Previous work has also shown that a higher parasite burden significantly delays parasite clearance among children 21 , as well as increases the risk of severe malaria 3,4 .…”
Section: Determinants Of Parasite Clearance Timementioning
confidence: 90%
“…In 2010, of the 5819 reported cases, approximately 60% were due to P. vivax [ 3 ]. Moreover, the potential for reactivation of dormant hypnozoites creates a number of difficulties for the elimination of malaria in the country [ 73 ]. The dramatic reduction of P. vivax observed in the present study also follows a steady increase in notification rate of P. malariae / P. knowlesi .…”
Section: Discussionmentioning
confidence: 99%